Fundamental Frequency in Sentence Production - Cooper, W. E. author. aut Link
X, 213 p.
Keywords: The scientific study of speech production has been undertaken within a variety of disciplines, including linguistics, physiology, physical acoustics, and psychology, among others. In recent years, it has become possible to combine the knowledge accumulated within these separate disciplines to gain more insight into the nature of this complex human activity. Here, we apply an interdisciplinary focus to one of the most widely discussed and poorly under stood aspects of the speech signal. This study of fundamental voice frequency involves a mixture of linguistics, physical acoustics, and psychology. The rele vant aspects of each discipline are introduced in Chapter 1 so that readers with minimal background in at least one of these areas should be able to compre hend much of the whole. This book is written primarily as an original research treatise rather than as a review of the literature. However, many previous studies of fundamental fre quencyare discussed here, and the book should serve as both a reference source and a supplementary text in courses on speech communication taught within a number of disciplines. Because of the complexity of Fo patterns, graphical displays of the results playa particularly important role in this presentation. While the results of each experiment are summarized and discussed verbally within the text, the graphical displays, by comparison, represent a more inte gral part of this book than is often the case in treatments of speech production.